Earth observation for drought risk financing in pastoral systems of sub-Saharan Africa - Fava, Francesco P.; Vrieling, Anton (Elsevier, 2021)
As climate-related crises increase globally, climate risk financing is becoming an integral part of financial protection and resilience building strategies of African countries. Drought-induced crises result in devastating human impacts and high costs for vulnerable countries, threatening longer-term investments and development efforts. While earth observation (EO) has been widely used for drought early warning, new opportunities emerge from integrating EO data and methods into index-based drought risk financing (IBDRF) instruments. Such instruments aim at supporting an effective and timely response during drought shocks and improving the resilience of small-holder farmers and livestock keepers. This review documents the current status, and discusses future prospects and potential challenges for EO utilization in IBDRF applications in sub-Saharan Africa. We focus on pastoral systems, which are hotspots in terms of vulnerability to climate and environmental change, food insecurity, poverty, and conflicts. In these systems, EO-based IBDRF interventions are rapidly scaling up as part of national and international risk management strategies.